SECURITY OF COMPUTER NETWORK FUNCTIONING BASED ON A NEURON MODEL OF OVERLOAD CONTROL - TOROSHANKO, OLEKSANDR; AFANASIEV, PAVLO; ISHCHUK, IHOR; TOROSHANKO, YAROSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The method of ensuring the operation security of computer network based on the proposed overload prediction and detection scheme is considered. Congestion management is performed by adjusting the incoming data flow and analyzing the network performance sensitivity function. The gradient of the sensitivity function characterizes the rate of change of this function and provides the optimal direction for adjusting the speed of the data source. The results of a comparative analysis of congestion control methods based on the analysis of the queue length and the sensitivity indicator with 1- and 3-step horizons by predicting the state of the network are presented.